Analisis Kualitas Batubara Berdasarkan Analisis Proksimat, Total Sulfur dan Kalori di Site Jhonlin Group PT Tribhakti Inspektama: Coal Quality Analysis Based on Proximate Analysis, Total Sulfur and Calories at the Jhonlin Group Site, PT Tribhakti Inspektama - Bakri, Suriyanto; Widodo, Sri; Arifin, Mubdiana; Ardana, Rifal (CV Insight Publisher, 2025)
Coal is one of the fossil energy sources that remains the backbone of national energy needs, especially in the power generation and processing industries. The quality of coal greatly determines its economic value and efficiency of use, so a comprehensive analysis of coal characteristics is needed to determine its suitability for industry specifications and end-user requirements. PT Tribhakti Inspektama, as an independent inspection agency operating in the Jhonlin Group's working area, plays an important role in testing and monitoring the quality of coal to be marketed. This study aims to analyze coal quality based on the results of proximate analysis, total sulfur content, and calorific value in the Jhonlin Group mining area. The research method was carried out by taking coal samples from the stock file, preparing them, and analyzing them in the laboratory. The results of the study show that the proximate analysis of the samples was 4.13% ash, 20.87% moisture content, 42.21% volatile matter, and 32.77% fixed carbon. The coal in the study area is categorized as lignite with a low to sub-bituminous rating, so it still has the potential to be used for the cement industry and coal-fired power plants.